2020
DOI: 10.1002/smtd.202000920
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐/Nano‐Structures on Biodegradable Magnesium@PLGA and Their Cytotoxicity, Photothermal, and Anti‐Tumor Effects

Abstract: The size and structural control of particulate carriers for imaging agents and therapeutics are constant themes in designing smart delivery systems. This is motivated by the causal relationship between geometric parameters and functionalities of delivery vehicles. Here, both in vitro and in vivo, the controlling factors for cytotoxicity, photothermal, and anti‐tumor effects of biodegradable magnesium@poly(lactic‐co‐glycolic acid (Mg@PLGA) particulate carriers with different sizes and shell thicknesses are inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…Firstly, the thermal conductivity of pure Mg is higher than that of MAO [ 32 ], which benefited the transfer of heat from the surface of the substrate to the solution. Secondly, the increased temperature of the solution further promoted the corrosion of pure Mg and produced heat [ 36 , 66 ]. As shown in Figure 7 d, the temperature of the MAO/PMTMS@(Hemin-CaP) coating exhibited a stable on-off behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, the thermal conductivity of pure Mg is higher than that of MAO [ 32 ], which benefited the transfer of heat from the surface of the substrate to the solution. Secondly, the increased temperature of the solution further promoted the corrosion of pure Mg and produced heat [ 36 , 66 ]. As shown in Figure 7 d, the temperature of the MAO/PMTMS@(Hemin-CaP) coating exhibited a stable on-off behavior.…”
Section: Resultsmentioning
confidence: 99%
“…In vivo experiments, Mg particles exhibit excellent photothermal effects for tumor eradication and Mg ions released from PLGA/Mg porous scaffolds could promote bone regeneration, which gives the PLGA/Mg scaffolds dual functions of inhibiting OS recurrence and continuously repairing bone defects. On the other hand, after intra-tumoral injection, Zhou et al found that micro-scale Mg/PLGA exhibited stronger cytotoxicity, PTT, and anti-tumor effect than nano-scale Mg/PLGA ( Zhou et al, 2021 ). This inspires the design of Mg scaffolds in the reconstruction of bone defects after osteosarcoma surgery.…”
Section: Magnesium Zinc and Their Alloymentioning
confidence: 99%
“…2 Magnesium, zinc, and their alloy Mg, Zn, and their alloys exert excellent anti-tumor effects by influencing the metabolism and phenotype of tumor cells, inducing tumor cell proliferation inhibition, cell cycle arrest, and cell apoptosis (Krol et al, 2017;Zhou et al, 2021). Studies by Wu et al have shown that magnesium-zinc alloy can inhibit the proliferation of osteosarcoma cell line U20S cells by arresting the G2/M phase of the cell cycle, and promote the apoptosis of U20S tumor cells through a mitochondrial-dependent pathway; at the same time, the alloy solution can inhibit the metastasis of U20S tumor cells through the MAPK pathway (Wu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The photothermal and anti-tumor effects of MgPLGA spheres were determined by their Mg content, irrelevant to their structural features and size, as shown in in vitro cell assays and in vivo mice models. These results provided important implications for designing and fabricating stimuli-responsive drug delivery vehicles [90]. Subha et al used beeswax and PLGA as wall materials in order to obtain sustained and controlled release of Capecitabine, an anticancer drug [91].…”
Section: Plga Microparticlesmentioning
confidence: 99%